1994
DOI: 10.1016/0741-5214(94)90224-0
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and patterns of aortic aneurysms in young patients

Abstract: Aneurysmal disease presenting in the young adult is more likely to be symptomatic and associated with more proximal aortic involvement than aneurysmal disease in older patients. Smoking appears to play an important role in the pathogenesis of aneurysmal disease in the young patient and was associated in our study with more proximal aneurysms among older patients. A subgroup of patients at risk for early and aggressive aneurysm disease is suggested by these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 15 publications
1
34
0
8
Order By: Relevance
“…Although the UK surgical cohort now has a lower overall mortality rate than the nonoperative cohort (p Most AAAs are asymptomatic and are discovered incidentally on routine physical examination or on an abdominal roentgenogram (969) or an ultrasound scan that has been performed for other indications. Younger patients are more likely to be symptomatic at the time of diagnosis (970). Pain is the most frequent complaint in patients with symptomatic AAAs and usually is located in the hypogastrium or the lower part of the back.…”
Section: Aortic Aneurysm Rupturementioning
confidence: 99%
“…Although the UK surgical cohort now has a lower overall mortality rate than the nonoperative cohort (p Most AAAs are asymptomatic and are discovered incidentally on routine physical examination or on an abdominal roentgenogram (969) or an ultrasound scan that has been performed for other indications. Younger patients are more likely to be symptomatic at the time of diagnosis (970). Pain is the most frequent complaint in patients with symptomatic AAAs and usually is located in the hypogastrium or the lower part of the back.…”
Section: Aortic Aneurysm Rupturementioning
confidence: 99%
“…A high proportion of cases are symptomatic, and the process is very often associated with more proximal aortic involvement [27] . Many studies reported familial aggregation of abdominal aortic aneurysms [28] .…”
Section: Abdominal Aortic Aneurysms and Dissectionmentioning
confidence: 99%
“…Although the UK surgical cohort now has a lower overall mortality rate than the nonoperative cohort (p (92) 527 (93) Nonoperative cohort 327 (62) 349 ( Most AAAs are asymptomatic and are discovered incidentally on routine physical examination or on an abdominal roentgenogram (969) or an ultrasound scan that has been performed for other indications. Younger patients are more likely to be symptomatic at the time of diagnosis (970). Pain is the most frequent complaint in patients with symptomatic AAAs and usually is located in the hypogastrium or the lower part of the back.…”
Section: Aortic Aneurysm Rupturementioning
confidence: 99%